The role of language in building cultural identity - Al-Daraji, Asst. Prof. Dr. Hadeel Raad Tahseen Al-Daraji (Sulaimani Journal for Humanities, 2026)
Language plays a pivotal role in building cultural identity; it is not just a means of communication, but rather a vessel that contains the culture, history and values of peoples. Through it, we transmit cultural heritage from one generation to another, as it reflects the customs, traditions, proverbs and poems that distinguish each society. It carries, through its vocabulary and structures, an ancient culture that includes literature, poetry and philosophy, which enhances the individual's connection to his Arab culture and makes him part of its heritage, and a symbol of resistance and preservation of identity in the face of external cultural influences. It is a weapon to confront attempts at cultural obliteration. It is not just a means of communication, but rather a symbol of history and belonging.